Problem-Solving Ability and Self-Efficacy: The Effect of Mathematics Instruction-Based Theory of Didactical Situation - Jatisunda, Mohamad Gilar; Saefuloh, Nandang Arif; Utami, Wulan Putri (Jurnal Pendidikan Matematika, 2025)
This study investigates how Theory of Didactical Situations-based mathematics training affects problem-solving and self-efficacy. A quasi-experimental approach with pre- and post-tests and a control group was used in this study. The research sample comprised 58 students and was allocated into two groups: an experimental group, which received TDS intervention, and a control group, which received traditional explanatory learning. The two-way analysis of variance (ANOVA) results indicated a substantial interaction between the teaching methods employed in mathematics instruction, the early mathematical skills of the students (EMS), and the link between class and EMS. This interaction significantly improved students' capacity to solve arithmetic problems. Similarly, these characteristics have a notable impact on the degree of self-efficacy. The study emphasises the practical consequences of the necessity for teachers to consider students' cognitive abilities when planning mathematics instruction carefully. Additionally, it underscores the importance of designing learning environments that align with specific learning goals. This study further enhances the existing empirical evidence about the correlation between the learning environment, mathematical problem-solving abilities, and self-efficacy. Penelitian ini menguji efek dari pengajaran matematika berbasis Teori Situasi Didaktis terhadap kemampuan pemecahan masalah matematika dan efikasi diri. Penelitian ini menggunakan desain kuasi-eksperimental yang menampilkan kerangka kerja pre-test dan post-test, serta melibatkan kelompok kontrol. Sampel penelitian terdiri dari 58 siswa yang dialokasikan ke dalam dua kelompok: kelompok eksperimen, yang menerima intervensi TDS, dan kelompok kontrol, yang menerima pembelajaran eksplanatori tradisional. Hasil analisis varians (ANOVA) dua arah menunjukkan adanya interaksi yang substansial antara metode pengajaran yang digunakan dalam pembelajaran matematika, kemampuan awal matematika siswa (EMS), dan hubungan antara kelas dan EMS. Interaksi ini secara signifikan meningkatkan kemampuan siswa dalam memecahkan masalah aritmatika. Demikian pula, karakteristik ini memiliki dampak penting pada tingkat efikasi diri. Penelitian ini menekankan konsekuensi praktis yang muncul dari perlunya guru mempertimbangkan kemampuan kognitif siswa ketika merencanakan pengajaran matematika dengan hati-hati. Selain itu, penelitian ini juga menggarisbawahi pentingnya merancang lingkungan belajar yang selaras dengan tujuan pembelajaran yang spesifik. Penelitian ini semakin memperkuat bukti empiris yang ada tentang korelasi antara lingkungan belajar, kemampuan pemecahan masalah matematika, dan efikasi diri.